Seasonal modulation of oceanic seismicity in the azores - Lordi, Ana L.; Neves, Maria C.; Custódio, Susana; Dumont, Stéphanie (Frontiers in Earth Science, 2022)
The analysis of an 11-year (2008-2018) seismic catalogue of the Azores suggests the existence of secondary cyclic influences on the seismicity rate of the oceanic region, with more earthquakes observed during the summer months, from May to August, than in winter. Statistical testing based on Monte-Carlo simulations and a Jack-Knife methodology indicate that the seasonal modulation affects earthquakes with magnitudes M3.3-4.5, well above the magnitude of completeness. Here, we investigate the seasonal variations of earthquake rate considering both the whole Azores oceanic domain and four separate sub-regions, corresponding to four regional clusters identified by previous authors. The analysis shows that the seasonal modulation is particularly observed near the Triple Junction region between the Faial Island and the Mid-Atlantic Ridge. To identify possible mechanisms driving the seasonal modulation, we apply Singular Spectral Analysis to the seismicity rate and to time-series of plausible external triggers, in order to investigate possible common periodicities. We find significant correlations between the earthquake rate, sea level anomaly rate, GRACE satellite anomalies and ocean bottom pressure, suggesting that water load may modulate the Azores oceanic seismicity.